2022
DOI: 10.1002/ehf2.13884
|View full text |Cite
|
Sign up to set email alerts
|

Suspicion, screening, and diagnosis of wild‐type transthyretin amyloid cardiomyopathy: a systematic literature review

Abstract: Wild-type transthyretin amyloid cardiomyopathy (ATTRwt CM) is a more common disease than previously thought. Awareness of ATTRwt CM and its diagnosis has been challenged by its unspecific and widely distributed clinical manifestations and traditionally invasive diagnostic tools. Recent advances in echocardiography and cardiac magnetic resonance (CMR), non-invasive diagnosis by bone scintigraphy, and the development of disease-modifying treatments have resulted in an increased interest, reflected in multiple pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 157 publications
(830 reference statements)
0
8
0
Order By: Relevance
“…Transthyretin amyloid cardiomyopathy (ATTR‐CM) is an underrecognized fatal disease characterized by extracellular deposition of misfolded transthyretin proteins causing heart failure (HF) 1 . Previous studies on ATTR‐CM prevalence have mostly been performed retrospectively and in selected cohorts 2–4 . A recent community screening study found that ATTR‐CM, defined in this study by a Perugini grade ≥2 out of three cardiac tracer uptake on bone scintigraphy, was present in 6% of patients older than 60 years with HF with preserved ejection fraction (HFpEF) and left ventricular hypertrophy (LVH) 5 .…”
Section: Variables All Subjects (N = 104) Attrwt‐cm (N = 5) Attrwt‐cm...mentioning
confidence: 93%
See 1 more Smart Citation
“…Transthyretin amyloid cardiomyopathy (ATTR‐CM) is an underrecognized fatal disease characterized by extracellular deposition of misfolded transthyretin proteins causing heart failure (HF) 1 . Previous studies on ATTR‐CM prevalence have mostly been performed retrospectively and in selected cohorts 2–4 . A recent community screening study found that ATTR‐CM, defined in this study by a Perugini grade ≥2 out of three cardiac tracer uptake on bone scintigraphy, was present in 6% of patients older than 60 years with HF with preserved ejection fraction (HFpEF) and left ventricular hypertrophy (LVH) 5 .…”
Section: Variables All Subjects (N = 104) Attrwt‐cm (N = 5) Attrwt‐cm...mentioning
confidence: 93%
“…1 Previous studies on ATTR-CM prevalence have mostly been performed retrospectively and in selected cohorts. [2][3][4] A recent community screening study found that ATTR-CM, defined in this study by a Perugini grade ≥2 out of three cardiac tracer uptake on bone scintigraphy, was present in 6% of patients older than 60 years with HF with preserved ejection fraction (HFpEF) and left ventricular hypertrophy (LVH). 5 Early distinction of ATTR-CM from other common HFpEF types is crucial, especially with disease-specific treatment available.…”
Section: Prevalence Of Wild-type Transthyretin Amyloidosis In a Prosp...mentioning
confidence: 95%
“… 14 , 16 Although these so‐called ‘red flags’ are obvious candidates to utilize for ATTR screening, their sensitivity and specificity have yet to be fully investigated. 17 …”
Section: Introductionmentioning
confidence: 99%
“…14,16 Although these so-called 'red flags' are obvious candidates to utilize for ATTR screening, their sensitivity and specificity have yet to be fully investigated. 17 The primary aim of this study was to examine the prevalence of ATTRwt in an aged (≥60 years) and predominantly male population with idiopathic CTS release surgery within the past 1-6 years. The secondary aim was to characterize the cardiac disease stage of patients with ATTRwt identified by screening compared with clinically diagnosed patients with symptomatic ATTRwt matched by gender, age, and previous CTS surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation